Restaurování granátových šperků - Pecenová, Zuzana; Děd, Jiří; Prášil, Jaroslav (Univerzita Pardubice, 2014)
The work deals with restoration of set of garnet jewellery. The set consist of a segmented necklace and segmented bracelet. Determination of the base metal composition was performed by electron microanalysis. The authenticity of garnets was confirmed by refractive index. The jewellery was degreased in ethanol. Corrosion products were partially removed mechanically by a fine brass brush. Missing parts of necklace and bracelet was made of alloy which composition similar to the original metal. Missing stones were supplied with pyropes with rue cut. A paper and aluminium foil was put under stones before they were mounted into the jewellery. The production of new parts and inserting of stones were made by original technology. Where the stone trims were damaged a two‐component epoxy resin was used. Conservation of metal surface was made by Paraloid B72 coating. The part of this restoration work was adjustment of etui for jewellery. Scratched paper was replaced by coloured Japanese paper. The final appearance was made and the missing lock staple was replenished. The surface was then retouched with stabile water colour. The storage conditions were also recommended.
Restoration and conservation of garnet jewellery